Association between metabolic deteriorations and prior gestational diabetes according to weight status. (29th November 2014) - Vigneault, Jessica; Lemieux, Simone; Garneau, Véronique; Weisnagel, S. John; Tchernof, André; Robitaille, Julie
<x xml:space="preserve">Abstract</x> Objective The aim of the present study is to investigate the effect of prior gestational diabetes mellitus (GDM) on glucose and insulin homeostasis according to weight status. Methods The analysis included 299 women, 216 with [GDM(+)] and 83 without prior GDM [GDM(−)]. The mean time between pregnancy and testing was 3.9 years. Glucose values were obtained from a 2‐h 75 g oral glucose tolerance test (OGTT). Body composition was measured by dual‐energy X‐ray. Results In women with normal BMI, fasting glucose, 2‐h post‐OGTT glucose, and HbA1 were higher for GDM(+) (P < 0.05). Normal‐weight women with GDM(+) presented lower HOMA‐IS, insulin secretion, and insulinogenic index (P < 0.05) compared to GDM(−). Body fat and android fat mass were higher, gynoid fat mass was similar, and lean body mass was decreased in GDM(+) vs. GDM(−) with normal weight (P < 0.05). A greater proportion of GDM(+) with overweight/obesity had prediabetes (72.1%) or type 2 diabetes (T2D) (21.7%) vs. GDM(−) and overweight/obesity (17.1 and 2.4%) or GDM(+) and normal weight (60.5 and 14.0%). Conclusions A combination of GDM and overweight/obesity is associated with T2D‐related metabolic deteriorations. Nevertheless, normal‐weight women with GDM(+) had increased android fat and greater metabolic complications, suggesting that women with prior GDM should benefit from lifestyle intervention, regardless of their weight status.